1998
DOI: 10.1021/la9707181
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Microscopy of Molecular Adsorbates at the Liquid−Solid Interface:  Functional Group Variations in Image Contrast

Abstract: Recent studies have demonstrated that functionalized portions of long-chain hydrocarbons (CH3(CH2) n X, where X = SH, S, SS, NH2, Br, I) physisorbed on graphite at the liquid−solid interface exhibit enhanced contrast (increased tunneling current) when imaged by scanning tunneling microscopy (STM). The tunneling mechanism for such molecules can be investigated by examining the interplay between topographic and electronic structure/coupling factors. Utilizing a scanning tunneling spectroscopy methodology, change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
80
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 26 publications
9
80
0
2
Order By: Relevance
“…Although a direct comparison of different alkyl derivatives is generally complicated by the presence of both electronic and geometric factors, the image contrast observed in the present work is in agreement with previous observations of bright bromine and iodine substituents (17,41,61) and dark fluorine substituents observed at liquid-solid interfaces (17,62).…”
Section: Stm Image Contrast: Electronic and Spatial Factorssupporting
confidence: 92%
See 2 more Smart Citations
“…Although a direct comparison of different alkyl derivatives is generally complicated by the presence of both electronic and geometric factors, the image contrast observed in the present work is in agreement with previous observations of bright bromine and iodine substituents (17,41,61) and dark fluorine substituents observed at liquid-solid interfaces (17,62).…”
Section: Stm Image Contrast: Electronic and Spatial Factorssupporting
confidence: 92%
“…STM images recorded under ambient conditions showed that long 1-bromoalkanes formed self-assembled monolayers at the liquid͞solid interface, where adjacent lamellae are in a head-to-head configuration (as they are in the UHV STM images of the present work) but with a rectangular structure, ϭ 90°( unlike the UHV data where Х 60°) (17,41,61). Energy minimizations based on this initial configuration were found to lead inevitably to the angled structure shown in Fig.…”
Section: Stm Image Contrast: Electronic and Spatial Factorsmentioning
confidence: 48%
See 1 more Smart Citation
“…[9][10][11] These studies are complementary to our observations, which show little observable dependence on bias polarity of the mesogen unit in both specimens examined, while the contrast variation is solely associated with the methylene portion. It is therefore reasonable to conclude that the contrast of the mesogen unit does not contribute to the observed contrast reversal of the methylene units.…”
supporting
confidence: 84%
“…[9][10][11] The variation in vertical contrast of the functional groups of various alkane derivatives relative to the methylene units was affected by both topographic and electronic factors, with ionization potential (IP) accounting for the observed contrast. A lower IP leads to higher contrast in the STM images.…”
mentioning
confidence: 99%